Limited restoration of T cell subset distribution and immune function in older people living with HIV-1 receiving HAART - Na Li; Hong-Yi Zheng; Wei Li; Xiao-Yan He; Mi Zhang; Xia Li; Ren-Rong Tian; Xing-Qi Dong; Zhi-Qiang Shen; Yong-Tang Zheng (Immunity & Ageing)
Abstract Background Older people living with HIV-1 (PLWH) experience a dual burden from the combined effects of aging and HIV-1 infection, resulting in significant immune dysfunction. Despite receiving HAART, immune reconstitution is not fully optimized. The objective of this study was to investigate the impact of aging and HAART on T cell subsets and function in PLWH across different age groups, thereby providing novel insights into the prognosis of older PLWH. Method This study was conducted at Yunnan AIDS Care Center, China, to explore the immunological responses of old PLWH to HAART and compared with the middle-age and the younger. Blood samples were collected from 146 PLWH to analyze T cell subsets and their functions, with a particular emphasis on markers related to T cell differentiation, activation, exhaustion, inflammation, and cellular function, using multicolor flow cytometry analysis. Results Older age may have a greater effect on long-term CD4+T cell recovery. Compared with young and middle-aged PLWH, older PLWH presented distinct alterations in their immune profile, including a decline in the Naïve CD4+T and CD8+T cell subsets, an expansion of effector memory cells, and other potential immune risk phenotypes, such as activation, exhaustion, and up-regulation of aging markers. In addition, we observed a significant association between the CD4 + EM3 subset and the CD8 + EM2 subset with HIV-1 progression, independent of age, suggesting their potential as reliable markers for assessing immune reconstitution in all PLWH. Conclusion Our study extends previous findings showing that older participants exhibit a wide range of late differentiation, senescence, or exhaustion phenotypes in cells, including all the CD4+T and CD8+T subsets, consistent with an immunosenescent phenotype. This may accelerate poor immune recovery in older PLWH. Identifying new strategies to improve the immune risk phenotypes of older PLWH may help improve their immune reconstitution outcomes. The CD4 + EM3 subset and the CD8 + EM2 subset should be studied as additional markers of late presentation.